Long-term effect of fertilization and manuring on soil aggregate carbon mineralization - YADAV, RAJENDRA KUMAR; PURAKAYASTHA, T J; AHMED, NAYAN; DAS, RUMA; CHAKRABARTY, BIDISHA; BISWAS, SUNANDA; SHARMA, V K; SINGH, POOJA; TALUKDAR, DAIZEE; MOURYA, K K; WALIA, S S; SINGH, ROHITASAV; et al. (The Indian Journal of Agricultural Sciences, 2021)
The 32 years impact of manuring and fertilization on carbon mineralization in macro- and micro-aggregates in major soil groups of India was studied. Mollisol, Inceptisol, Vertisol, and Alfisol samples were collected (0-15 cm soil depth) from the treatments comprising of control, 100% NPK, 50%NPK+50% N-FYM, 50%NPK+50%N-WR (Wheat residue), 50% NPK + 50% N-GM (Green manure) in the year 2015. The results showed that the mineralizable C pool was significantly higher in treatments applied with 50%NPK+50%N-GM in Mollisol and Vertisol. In Alfisol and Inceptisol, 50% NPK+50% N-FYM and 50% NPK+50% N-GM were significantly higher in both macroaggregates and micro-aggregates protected carbon. Supplementation of fertilizer N either through FYM or various green manuring crops like Sesbania (Sesbania aculeata L. in Inceptisol), greengram (Vigna radiata L. in Mollisol), sunhemp (Crotalaria juncea L. in Vertisol) and karanj (Pongamia pinnata L. in Alfisol) significantly improved mineralizable carbon pool signifying their potential contributions to nutrient cycling and thereby nutrient availability to various crops in the cropping systems in the above soils.